Use of a cloned DNA fragment to analyze the fate of donor DNA in transformation of Streptococcus pneumoniae. - Méjean, V (1984)
The integration of donor label into the recipient fragment is followed during transformation of Streptococcus pneumoniae. The method used involves gel analysis of restriction endonuclease-treated recipient DNA after recombination with a radioactively labeled homologous cloned fragment.